TAVI durability. (25th November 2020) - Ziviello, F; Di Stefano, D; Joannes, F; Ancona, M.B; Bellini, B; Russo, F; Ferri, L; Carlino, M; Montorfano, M; Chieffo, A
Abstract: Background: TAVI (Transcatheter aortic valve implantation) is now established as the preferred treatment option for patients with symptomatic severe aortic stenosis at prohibitive or high surgical risk and its application is increasingly supported by an accumulating evidence base in patients at intermediate and low risk, but the issue of valve durability are still unsettled. Purpose: To evaluate long-term clinical outcomes and bioprosthesis valve dysfunction after TAVI. Methods: All patients treated with transfemoral TAVI, from November 2007 to December 2014 were analyzed. Baseline clinical, procedural and in-hospital outcomes were collected and revised. Clinical and echocardiographic follow-up was conducted either by clinic visits or telephone consultations. All definitions of the clinical endpoints and bioprosthesis valve failure used were in concordance with the Valve Academic Research Consortium 2 and the European Society of Cardiology consensus, respectively. Results: Four hundred and eight patients were included in the analysis. Median follow-up was 2.733 days (7.5 years), with the longest follow-up at 4.096 days (11.2 years). At 7.5 years (IQR 5.4–9.3 years), all-cause mortality was 64.5% (n=263), of these cardiovascular death was adjudicated in 33.6% (n=137), non-cardiovascular death in 30.9% (n=126) and valve-related death was 1.9% (n=8). Structural valve deterioration occurred in 2.9% (n=12), non-structural valve deterioration in 0.2% (n=1), thrombosis in 2.2% (n=9) and endocarditis in 3.2% of patients (n=13). Fourteen patients (3.4%) required surgical (1.2%) or percutaneous (2.2%) aortic valve re-intervention. Conclusions: Percutaneous aortic bioprosthesis demonstrated a low bioprosthesis valve failure at a median of 7.5 years of clinical follow-up after implantation, with low rate of degeneration or need of re-intervention. Overall mortality was high with acceptable rates of cardiovascular mortality and low rates of valve-related deaths. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): EAPCI Education and Training Grants